Best Answer

Pierre de Fermat's laatste stelling

(x, y, z, n) element van de (N +) ^ 4

n> 2

(a) element van de Z

F is de functie (s).

F (a) = [a (a +1) / 2] ^ 2

F (0) = 0 en F (-1) = 0

Beschouw twee vergelijkingen.

F (z) = F (x) + F (y)

F (z-1) = F (x-1) + F (y-1)

We hebben een keten van gevolgtrekking

F (z) = F (x) + F (y) gelijkwaardig F (z-1) = F (x-1) + F (y-1)

F (z) = F (x) + F (y) conclusie F (z-1) = F (x-1) + F (y-1)

F (z-x-1) = F (x-x-1) + F (y-x-1) conclusie F (z-x-2) = F (x-x-2) + F (y-x-2)

zien we

F (z-x-1) = F (x-x-1) + F (y-x-1)

F (z-x-1) = F (-1) + F (y-x-1)

F (z-x-1) = 0 + F (y-x-1)

conclusie

z = y

en

F (z-x-2) = F (x-x-2) + F (y-x-2)

F (z-x-2) = F (-2) + F (y-x-2)

F (z-x-2) = 1 + F (y-x-2)

conclusie

z = / = y.

conclusie

F (z-x-1) = F (x-x-1) + F (y-x-1) geen conclusie (z-x-2) = F (x-x 2) + F (y-x-2)

conclusie

F (z) = F (x) + F (y) geen conclusie F (z-1) = F (x-1) + F (y-1)

conclusie

F (z) = F (x) + F (y) zijn niet equivalent van F (z-1) = F (x-1) + F (y-1)

Daarom is de twee gevallen.

[F (x) + F (y)] = F (z) en F (x-1) + F (y-1)] = / = F (Z-1)

of vice versa

conclusie

[F (x) + F (y)] - [F (x-1) + F (y-1)] = / = F (z) - F (z-1).

of

F (x) - F (x-1) + F (y)-F (y-1) = / = F (z) - F (z-1).

zien we

F (x) - F (x-1) = [x (x 1) / 2] ^ 2 - [(x-1) x / 2] ^ 2

= (X ^ 4 +2 x ^ 3 + x ^ 2/4) - (x ^ 4-2x 3 + x ^ ^ 2/4).

= X ^ 3

F (y)-F (y-1) = y ^ 3

F (z)-F (z-1) = z ^ 3

conclusie

x 3 + y ^ 3 = / = z ^ 3

n> 2. lossen soortgelijke

We hebben een keten van gevolgtrekking

G (z) * F (z) = G (x) * F (x) + G (y) * F (y) gelijkwaardig G (z) * F (z-1) = G (x) * F ( x -1) + G (y) * F (y-1)

G (z) * F (z) = G (x) * F (x) + G (y) * F (y) conclusie G (z) * F (z-1) = G (x) * F (x -1) + G (y) * F (y-1)

G (z) * F (z-x-1) = G (x) * F (x-x-1) + G (y-x-1) * F (y) conclusie G (z) * F (z-x-2) = G ( x) * F (x-x 2) + G (y) * F (y-x 2)

zien we

G (z) * F (z-x-1) = G (x) * F (x-x-1) + G (y) * F (y-x-1)

G (z) * F (z-x-1) = G (x) * F (-1) + G (y) * F (y-x-1)

G (z) * F (z-x-1) = 0 + G (y) * F (y-x-1)

conclusie

z = y.

en

G (z) * F (z-x-2) = G (x) * F (x-x-2) + G (y) * F (y-x-2)

G (z) * F (z-x-2) = G (x) * F (-2) + G (y) * F (y-x-2)

G (z) * F (z-x-2) = G (x) + G (y) * F (x-y-2)

x> 0 conclusie G (x)> 0

conclusie

z = / = y.

conclusie

G (z) * F (z-x-1) = G (x) * F (x-x-1) + G (y-x-1) * F (y) geen conclusie G (z) * F (z-x-2) = G (x) * F (x-x-2) + G (y) * F (y-x-2)

conclusie

G (z) * F (z) = G (x) * F (x) + G (y) * F (y) geen conclusie G (z) * F (z-1) = G (x) * F ( x-1) + G (y) * F (y-1)

conclusie

G (z) * F (z) = G (x) * F (x) + G (y) * F (y) zijn niet equivalent van G (z) * F (z-1) = G (x) * F (x-1) + G (y) * F (y-1)

Daarom is de twee gevallen.

[G (x) * F (x) + G (y) * F (y)] = G (z) * F (z) en [G (x) * F (x-1) + G (y) * F (y-1)] = / = G (z-1) * F (z-1)

of vice versa

conclusie

[G (x) * F (x) + G (y) * F (y)] - [G (x) * F (x-1) + G (y) * F (y-1)] = / = G (z) * [F (z) -F(Z-1)].

of

G (x) * [F (x) - F (x-1)] + G (y) * [F (y) - F (y-1)] = / = G (z) * [F (z) - F(z-1)]

zien we

x ^ n = G (x) * [F (x) - F (x-1)]

y ^ n = G (y) * [F (y) - F (y-1)]

z ^ n = G (z) * [F (z) - F (z-1)]

conclusie

x ^ n + y ^ n = / = z ^ n

gelukkig en vrede

Tran tan Cuong .

Study guides

☆☆

Q: What is grace solve about Fermat?

Write your answer...

Submit

Still have questions?

Related questions

Andrew Wiles

Fermat's Last Theorem

long time.

Pierre de Fermat. The problem was called Fermat's Last Theorem

Fermat Prize was created in 1989.

Yes, the famous Fermat's Last Theorem, a conjecture by Fermat, that an equation of the form an + bn = cn has no integer solution, for n > 2. This was conjectured by Fermat in 1637, but it was only proved in 1995.Yes, the famous Fermat's Last Theorem, a conjecture by Fermat, that an equation of the form an + bn = cn has no integer solution, for n > 2. This was conjectured by Fermat in 1637, but it was only proved in 1995.Yes, the famous Fermat's Last Theorem, a conjecture by Fermat, that an equation of the form an + bn = cn has no integer solution, for n > 2. This was conjectured by Fermat in 1637, but it was only proved in 1995.Yes, the famous Fermat's Last Theorem, a conjecture by Fermat, that an equation of the form an + bn = cn has no integer solution, for n > 2. This was conjectured by Fermat in 1637, but it was only proved in 1995.

who meny juseph have fermat

It was 1647 not 1847 and by Fermat himself.

Fermat's Room was created on 2007-10-07.

A Fermat Prime refers to a proof that the mathematician Fermat discovered. It refers to a integer that is subject to an equation and the predictable result. Below is a webpage that explains it with examples.

Pierre De Fermat is famous for Fermat's Last Theorem, which states that an+bn=cn will never be true as long as n>2

Pierre de Fermat was born on August 17, 1601.